Divide and rule: Populist crackdowns and media elites in the Philippines. (October 2022) - Tapsell, Ross
This article examines the ways in which populist president Rodrigo Duterte has managed and controlled the Philippines media since his election victory in 2016. Existing literature has pointed to the important role the media has played in electing and sustaining the popularity of Duterte, but have not examined the role of 'media elites'. Through personal interviews with media owners and others in Manila, this empirical research provides insights into the challenges facing the contemporary Philippines media, in particular those media elites whose companies criticise his administration. While Duterte – like most populists – claims to be challenging powerful 'oligarchs', in reality his administration has cracked down severely against some media elites and has nurtured coercive relationships with others. The result is a landscape where media elites are unable to coalesce around media freedom. The research provides relevant findings supporting global literature on the role of populists in enabling greater crackdowns on the mainstream and independent media.